Backstepping-based robust-adaptive control of a nonlinear 2-DOF piezoactuator. (August 2015) - Escareno, Juan-Antonio; Rakotondrabe, Micky; Habineza, Didace
Abstract: This paper deals with the control of a two degrees of freedom (2-DOF) piezoelectric actuator for precise positioning and which exhibits strong hysteresis nonlinearity and strong cross-couplings. To tackle the nonlinearity and the cross-couplings, we propose two decoupled models in which they are considered as (fictive) external disturbances which require proper characterization. Then, a backstepping technique is proposed to construct a robust controller that merges sliding-mode and adaptive schemes. Extensive experimental tests are finally carried out to prove the efficiency of the modeling and control technique proposed.